2013
DOI: 10.19030/iber.v12i4.7738
|View full text |Cite
|
Sign up to set email alerts
|

Bank Credit And Agricultural Output In South Africa: A Cobb-Douglas Empirical Analysis

Abstract: We empirically examine the impact of bank credit on agricultural output in South Africa using the Cobb-Douglas production function. We utilize time series data of agricultural output, bank credit, capital accumulation, labour and rainfall from 1970 2009. With agricultural output as the dependent variable, we determine OLS estimates of the Cobb-Douglas production function. We observe that bank credit has a positive and significant impact on agricultural output in South Africa. With other factors of production k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 23 publications
3
37
0
3
Order By: Relevance
“…Similarly, a 1% increase in bank credit will result in a 0.49% increase in agricultural output holding other factors in the model constant. Similar results were obtained by Bashir (2010), Ahmad (2011) and Chisasa and Makina (2013) for South Africa using the Cobb-Douglas model.…”
Section: Cointegration Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, a 1% increase in bank credit will result in a 0.49% increase in agricultural output holding other factors in the model constant. Similar results were obtained by Bashir (2010), Ahmad (2011) and Chisasa and Makina (2013) for South Africa using the Cobb-Douglas model.…”
Section: Cointegration Resultssupporting
confidence: 88%
“…The main emphasis of this debate has centred on the impact of institutional credit on growth in agricultural output. Several empirical studies have adopted the Cobb-Douglas (1928) production function to estimate agricultural output function (Enoma, 2010;Sial et al, 2011;Chisasa and Makina, 2013). These studies have largely found credit to have a positive impact on agricultural output.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest types -Cobb-Douglas production functions -are the most widely used (Chisasa and Makina, 2013), but do not cope with complex systems like those in Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…The Cobb-Douglas Production functions are the most widely used types to depicts the production theory (Chisasa and Makina, 2013), while it cannot cope with the complex systems that with multiple inputs/multiple outputs production systems that influenced by natural resources, external environmental attributes, and the preferences of land managers. To address the multiple-inputs/multiple outputs production functions, the efficiency frontier method has become popular (Grosskopf et al, 1992), which can be traced back to the ideas put forward by Farrell (Farrell, 1957).…”
Section: Trade-off Analysis Based On Production Theorymentioning
confidence: 99%